探討科學想像力融入國小自然科課程單元之成效：以「簡單力學－力與運動」單元為例 Effectiveness of an Instructional Experiment Using Scientific Imagination Integrated Into a Nature Science Course for Elementary School Students: An Example of “Simple Machines − Force and Motion” - 王佳琪 Chia-Chi Wang; 楊棨棠 Chi-Tang Yang (Journal of Research in Education Sciences, 2019)
本研究目的旨在以科學想像力歷程模式為基礎，探討科學想像力融入國小自然科「簡單力學─力與運動」課程教材，是否能有效提升國小高年級學生的科學想像力及教學品質。研究設計採準實驗不等組前、後測設計，以臺南市某國小六年級兩班共 72 人為研究對象，分為實驗組 36 人與對照組 36 人，實驗教學為期五週。本研究使用「科學想像力情境測驗」為研究工具，包含漫想力、聯想力、奇想力及妙想力四個成分，分別在實驗教學前、後進行施測，並以兩組在實驗教學前後的差異分數，進行獨立樣本 t 檢定與效果量分析；同時，更輔以學生課堂發言、同儕互動紀錄及課程教學自我檢核，檢視學生科學想像力教學成效，以作為教學提升之回饋。研究結果指出，實驗組學生的科學想像力及課堂表現優於對照組學生，表示科學想像力融入自然科教學能顯著提升國小高年級學生的科學想像力，其結果對於未來科學教育融入想像力教學有正面成效。 This study primarily aimed to investigate the influence of the effectiveness of an instructional experiment employing scientific imagination integrated into a nature science course for elementary school students. In this study, quasi-experimental methods with a nonequivalent pretest-posttest design were used. This study included 72 elementary school students as participants. The participants were categorized into the experimental (n = 36) and control groups (n = 36). For the experimental group, a scientific imagination process was integrated into the nature science course for 5 weeks. The instruments of this study included a scientific imagination test-verbal (SIT-Verbal). An independent sample t test and Cohen’s d were used to examine the scientific imagination of students regarding the instructions. The results indicated that students who received scientific imagination teaching exhibited scientific imagination and class performance superior to that of students in the control group. This result indicates that the incorporation of scientific imagination into teaching can significantly increase the scientific imagination of students and does not deteriorate their performance in terms of learning science. The use of science education using imaginative teaching has a positive feedback.